2014
DOI: 10.1364/ao.53.000h27
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of wearable pupillometer for autonomic neuropathy of diabetic patients

Abstract: Diabetes is a familiar disease in modern society. In the early stage of diabetes, symptoms are unobvious, but they usually induce diabetic autonomic neuropathy or, worse, cardiovascular autonomic neuropathy. Pupillometers are effective instruments for observing human pupils. This article presents a novel wearable pupillometer design, without external light artifacts, and an embedded algorithm with blinking elimination, which investigates autonomic neuropathy through recording pupil dynamics triggered by an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…There was a significant smaller pupil size at scotopic and mesopic illumination conditions at the DM-group in comparison to AMD, RVO and the control group. This is consistent with previous studies [4,7,8].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…There was a significant smaller pupil size at scotopic and mesopic illumination conditions at the DM-group in comparison to AMD, RVO and the control group. This is consistent with previous studies [4,7,8].…”
Section: Discussionsupporting
confidence: 94%
“…The Parasympathetic and sympathetic pupillary dysfunction appears to be a common feature of autonomic impairment in diabetes mellitus [3] and is evidenced by diminished amplitude reflexes and significant smaller pupil diameter [1]. Furthermore, Ko et al, showed that the pupillary diameter is related to poor metabolic control, long diabetes duration, and also to other indices of microvascular diseases in patients with diabetes [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The American Diabetes Association recommends that neuropathy screening is performed every five years after diagnosis in Type 1 Diabetes Mellitus patients, and every year after diagnosis in Type 2 Diabetes Mellitus [5]. Therefore, it is not often expected to be affected by pupillary responses even in the absence of polyneuropathy in a population with an average of 4 years of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in organic electronics have proven their significance and competence in optoelectronic applications 1 2 3 4 5 6 . In particular, organic photosensors have been regarded promising due to their numerous potential applications in image sensing 7 8 9 , optoelectronic communication 3 4 5 6 , and health care monitoring 10 11 12 13 . They have been developed with various structures and operating mechanisms 14 such as photoconductors 15 16 , photodiodes 17 18 19 , phototransistors 20 21 22 , and photomemories.…”
mentioning
confidence: 99%